2019
DOI: 10.1037/apl0000396
|View full text |Cite
|
Sign up to set email alerts
|

An eye for an eye? A meta-analysis of negative reciprocity in organizations.

Abstract: Most models of negative workplace behaviors (NWB) are individual in nature, focusing on individual attitudes (e.g., satisfaction) and general workplace perceptions (e.g., procedural justice) that motivate NWB. Less commonly considered are explorations of relationally based negative workplace behaviors—how NWB from Party A is related to reciprocation of NWB from Party B. Based on 2 competing conceptualizations in the literature, that behavior is reciprocated “in-kind” in an eye for an eye exchange or that behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 267 publications
(307 reference statements)
7
57
0
Order By: Relevance
“…This suggests that in monetary payoffs trials, participants with greater negative reciprocity experience unexpected cooperation from opponents more unexpectedly and thus exhibit a larger dFRN following participants’ aggression. This finding supports several prior evidence demonstrating that the stronger preference for an eye for an eye or tit‐for‐tat (i.e., negative reciprocity) strategy always arises in the marketable orientated behavior (Banerjee & Mitra, 2018; Cox & Deck, 2005; Greco et al., 2019). Accordingly, when behavior is associated with monetary payoffs, participants have a stronger expectation that aggressive behavior should be returned in‐kind.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that in monetary payoffs trials, participants with greater negative reciprocity experience unexpected cooperation from opponents more unexpectedly and thus exhibit a larger dFRN following participants’ aggression. This finding supports several prior evidence demonstrating that the stronger preference for an eye for an eye or tit‐for‐tat (i.e., negative reciprocity) strategy always arises in the marketable orientated behavior (Banerjee & Mitra, 2018; Cox & Deck, 2005; Greco et al., 2019). Accordingly, when behavior is associated with monetary payoffs, participants have a stronger expectation that aggressive behavior should be returned in‐kind.…”
Section: Discussionsupporting
confidence: 89%
“…By examining a series of exchanges, our study provides a dynamic and realistic lens that allows for a better understanding of how reciprocity works. Although theories of social exchange often assume continuous interactions (Cropanzano et al, 2017; Greco et al, 2019), empirical research almost exclusively employs one-shot decisions (e.g., Aryee et al, 2002; Bishop & Scott, 2000; Cortina & Magley, 2003; Eisenberger et al, 2001; Glomb & Liao, 2003), providing a limited understanding of how people reciprocate over time. By focusing on the dynamic escalation of reciprocity rather than examining one-shot interactions (Halevy et al, 2012), our research gives insight into how and why cultural orientations and societal norms are formed and become reified over time.…”
Section: Discussionmentioning
confidence: 99%
“…As such, an alternative framework proposes that reciprocation can intensify over time (e.g., Andersson & Pearson, 1999; Baron & Neuman, 1996; Folger & Skarlicki, 1998; Hershcovis & Barling, 2010; Zand, 1972) and research has found several important factors that can explain the escalation of positive and negative reciprocity. Researchers focusing on the escalation of negative reciprocity have argued that relationships build “interpersonal heat” (Folger & Skarlicki, 1998; Greco et al, 2019) that progressively incites harsher retaliatory behavior. For example, Keysar et al (2008) demonstrate that, in a four-round dictator game, people escalate negative actions (i.e., in a “taking” game, leaving fewer resources to the target over time) but not positive actions (i.e., in a “giving” game, providing more resources to the target over time).…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…In other words, they suggested a link between the behaviors that are central to ethical leadership and those that convey high conscientiousness, both with respect to ethical conduct (Babalola, Bligh, Ogunfowora, Guo, & Garba, 2019). If a leader displays behaviors signaling dependability, self-discipline, responsibility, and high standards, the group is likely to develop norms consistent with these characteristics (Greco, Whitson, O'Boyle, Wang, & Kim, 2019). Ethical leaders, through their behavior (and in particular, their display of self-discipline, responsibility, and reliability), convey cues that signal high levels of conscientiousness, which the group will internalize (Kaptein, 2019).…”
Section: Ethical Leadership and Employee Well-beingmentioning
confidence: 99%